(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Introduction: Due to the complexity of the brain’s components, traditional autopsies frequently have difficulty detecting brain injuries. The development of virtual autopsies, which make use of cutting-edge imaging technology, presents an opportunity for forensic medicine. This abstract examines the use of virtual autopsy in forensic neuropathology and how it affects the identification of fatal brain injuries. Virtual autopsies have the potential to increase the precision and efficacy applying cutting-edge imaging techniques. Aim: This study aims to investigate the efficacy of virtual autopsy in diagnosing brain-related deaths. Methodology: This article focused on virtual autopsies in diagnosing brain-related deaths. Various sources were searched for relevant information, analyzing the methodology, advantages, and limitations. It resulted in 114 hits, with 60 articles initially selected. After analysis, the sample was reduced to 54, excluding 21 samples due to download issues. Quality concerns led to the elimination of 33 articles, leaving 7 for full-text analysis. Finally, 26 papers were chosen for the study (n=26). Result: Without intrusive procedures, virtual autopsy helps in identifying minor anomalies such as hemorrhages, wounds, malignancies, and infarctions. The non-invasive strategy improves diagnosis accuracy by lowering risks and making data storage, retrieval, and communication among professionals easier. Conclusion: Virtual autopsy in forensic medicine is increasingly utilized to identify brain-related fatalities. Precise brain imaging helps locate and assess complex abnormalities, aiding accurate diagnosis and potential advancements in forensic neuropathology. More research and technological development are necessary to enhance its diagnostic capabilities and transform forensic medicine.